2010
DOI: 10.1177/097135571001900206
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship and the Environment for Rural SMEs in the Shropshire Hills, UK, 1997–2009

Abstract: European agricultural and environmental policy has evolved considerably over the last 11 years. In this article the changes in farm businesses in an Environmentally Sensitive Area in South Shropshire are evaluated based upon two surveys with the same farmers in 1997 and 2008. The rate of participation in the environmental scheme had increased significantly at a time when Government led goals in this area had developed and become more output focussed. A combination of policy, market and animal health status cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
1
0
2
Order By: Relevance
“…There are numerous relevant studies on policy support. For example, Tate (2010) found through a survey of farmers in Shropshire, UK, that changes in European agricultural and environmental policies between 1997 and 2009 influenced the entrepreneurial behavior of farmers. Zhu and Kang (2013) found that policy support can positively influence the entrepreneurial intentions of farmers when they explored the logical relationship between the financial environment, policy support, and entrepreneurial intentions of farmers.…”
Section: Policy Support and Continuous Use Intentionmentioning
confidence: 99%
“…There are numerous relevant studies on policy support. For example, Tate (2010) found through a survey of farmers in Shropshire, UK, that changes in European agricultural and environmental policies between 1997 and 2009 influenced the entrepreneurial behavior of farmers. Zhu and Kang (2013) found that policy support can positively influence the entrepreneurial intentions of farmers when they explored the logical relationship between the financial environment, policy support, and entrepreneurial intentions of farmers.…”
Section: Policy Support and Continuous Use Intentionmentioning
confidence: 99%
“…Combina el trabajo de la tierra con otras actividades de tipo complementario. (Austin, Deary, Gibson, McGregor, & Dent, 1996), (Kodithuwakku & Rosa, 2002), (Eikeland & Lie, 1999), (Alsos et al, 2003), (McElwee, 2006), (Marchante, Varela, Guerrero, & Navarro, 2007), (Vesala, Peura, & McElwee, 2007), (Haugen & Jostein, 2008), (Gerard McElwee, 2008), (Andersson, Eklund, & Lehtola, 2009), (Schneider, 2009), (Tate, 2010), (Korsgaard, Müller, & Tanvig, 2015), (Soto Villagrán & Fawaz Yissi, 2016), (Viladomiu & Rosell, 2016), (Urquijo et al, 2017), (Radicic, Bennett, & Newton, 2017), (Anthopoulou, Kaberis, & Petrou, 2017), (Hansson & Kokko, 2018) Multifuncional El emprendedor basa su negocio rural, bajo una perspectiva pluriactiva, además de desarrollar diferentes funciones de la agricultura en su negocio y procura el desarrollo de prácticas sostenibles. (Foster, 1953), (Alsos et al, 2003), (Montiel Molina, 2003), (Gerard McElwee, 2008), (Andersson et al, 2009), (Aranda, Parrado, & Pachon, 2009), (Bosch & Gómez, 2010), (Cabus, 2010), (Seuneke, Lans, & Wiskerke, 2013), (González, Perpinyà, Tulla I Pujol, Martín, & Belmonte, 2014), (Guštin, Slavič, & Potočnik Slavič, 2015), (Seuneke & Bock, 2015),…”
Section: Pluriactivounclassified
“…Portafolio orientados al crecimiento, tomadores de riesgos, innovadores, optimistas y que tienen un mayor control personal sobre sus actividades comerciales. (Carter, 1998), (North & Smallbone, 2006), (G McElwee, 2006), (Vesala et al, 2007), (Gerard McElwee, 2008), (Haugen & Jostein, 2008), (Tate, 2010), (Seuneke et al, 2013), (Radicic et al, 2017) Emprendedor rural que se inserta y/o construye redes.…”
Section: Incrustaciónunclassified